Mitigate+: Food Loss and Waste country profile Colombia: Estimates of Food Loss and Waste, associated GHG emissions, nutritional losses, land use and water footprints - Axmann, H.; Guo, X.; Broeze, J.; Harbers, C.; Viquez-Zamora, M.; Soethoudt, J.M. (Wageningen University & Research, 2024)
FLW refers to all food intended for human consumption that is finally not consumed by humans. Food Loss is the decrease in the quantity or quality of food resulting from decisions and actions by food suppliers from the production stage in the chain, excluding retail, food service providers and consumers. Food Waste is the decrease in the quantity or quality of food resulting from decisions and actions by retailers, food services and consumers (FAO, 2019). Under this definition, FLW does not include food that is consumed in excess of nutritional requirements nor food that incurs a decrease of market value due to over-supply or other market forces, and not due to reduced quality.